A Comprehensive Review on Evaluating Talent Management Practices and its Underlying Factors (International Journal of Food and Nutritional Sciences, 2023)
The most critical challenge for today’s organizations is to manage their pool oftalent effectively. The managers need some strategic moves and practices to acquire,develop and retain the key employees